TRENDS OF CHILD'S UPBRINGING DIFFICULTIES IN FAMILY AND PRE-SCHOOL - Samuseviča, Alīda; Vikmane, Blāzma (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Based on findings of pre-school pedagogical and psychological theories on the importance of individualizing the socialization process in childhood, the authors of the paper detect the current typical difficulties of parents to nurture their children in family and the brightest children's undesirable behaviors in pre-school educational institutions. For children within the pre-school age group the nurturing effect from parents and the pedagogical values are particularly important. All the nuances of the family life and the system of mutual relationships create the specifics of child's individual socialization process. Authors of the paper emphasize and update the topicality of the democratic upbringing style in the family, characterize pedagogical reflection of pre-school teachers on contradictory trends of upbringing experiences of parents and the necessity to develop the pedagogical competence.